PENGARUH KUALITAS PRODUK, HARGA, PROMOSI, DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SANITARY WARE TOTO DI KOTA DENPASAR - Fernando, Made Fajar; Aksari, Ni Made Asti (E-Jurnal Manajemen; Vol 7 No 1 (2018), 2018)
Development in the sanitary business world is very rapid. Various innovations and modern technologies are used by various brands of sanitary ware. Toto is a world leading sanitary brand that became one of the pioneers who use modern technology and advanced machinery in producing its goods. This study aims to determine the effect of product quality, price, promotion, and distribution partially and simultaneously on  purchase decision of Toto Sanitary ware in Denpasar. By using purposive sampling technique, the number of samples used in this study is 100 respondent. Data were analyzed using multiple linear regression analysis. Based on the results of the study, it is found that the marketing mix consisting of product, price, promotion, and distribution simultaneously influence the purchase decision of Toto sanitary ware product in Denpasar. While partially, product, price, promotion, and distribution have positive and significant influence on the decision of purchasing Toto sanitary ware product in Denpasar. Thus it can be concluded that the marketing mix affects the purchase of Toto sanitary ware products in Denpasar.